Training manual for agricultural scientists - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Scientific writing for agricultural research scientists by Paul Stapleton (IPGRl) Anthony Youdeowei (WARDA), Joy Mukanyange (CTA) and Helen van Housen (ICRAF; 1995 128pp